The mechanism of action of oxytocin antagonist nolasiban in ART in healthy female volunteers. Issue 2 (August 2021) - Pierzyński, Piotr; Pohl, Oliver; Marchand, Line; Mackens, Shari; Lorch, Ulrike; Gotteland, Jean-Pierre; Blockeel, Christophe
Highlights: Uterine contractions at embryo transfer (ET) negatively correlate with pregnancy rates Uterine blood flow at ET is a predictor of uterine receptivity Oxytocin receptor antagonists, such as nolasiban, increase pregnancy rates after ET Nolasiban lowers contractions, alters endometrial genomics and increases perfusion Abstract: Research question: What are the effects of the oxytocin receptor (OTR) antagonist nolasiban on uterine contractions, endometrial perfusion and endometrial mRNA expression? Design: Randomized, double-blind, parallel-group, mechanism-of-action study with nolasiban. Forty-five healthy, pre-menopausal women were treated with placebo, 900 mg or 1800 mg nolasiban on the day corresponding to blastocyst transfer. Ultrasonographic uterine contraction frequency and endometrial perfusion were assessed, and endometrial biopsies analysed by next-generation sequencing. Results: Both doses of nolasiban showed decreased contraction frequency and increased endometrial perfusion depending on the time point assessed. At 1800 mg, 10 endometrial genes ( DPP4, CNTNAP3, CNTN4, CXCL12, TNXB, CTSE, OLFM4, KRT5, KRT6A, IDO2 ) were significantly differentially expressed (adjusted P < 0.05). Of these, OLFM4, DPP4 and CXCL12 were regulated in the same direction as genes involved in implantation during the window of implantation. In addition, three genes ( DPP4, CXCL12 and IDO2 ) were associated with decidualization and endometrial receptivity. Conclusions: These data expand our knowledge of the mechanism of action of nolasiban in increasing pregnancy rates after embryo transfer. The results suggest more marked effects of nolasiban 1800 mg compared with the 900 mg dose, supporting testing at higher doses in IVF patients.